Unlocking the critical drivers affecting quality of internal audit consulting services / Md Gulam Sharoar Hossain Khan, Noor Adwa Sulaiman and Suhaily Shahimi - Khan, Md Gulam Sharoar Hossain; Sulaiman, Noor Adwa; Shahimi, Suhaily (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
This study analysed how management support, organisational status, culture, data analytics, continuous audit, auditor independence, and internal auditor skills and competencies affect the quality of internal audit consulting services (CS) in risk management and strategy development. A survey was conducted among internal auditors (head, senior manager, manager) and customers (CEO, audit committee, CFO, manager, senior manager) of Bangladeshi listed companies. The survey data was analysed using SPSS and SmartPLS4 software. Results showed that management support, organisational status, culture, data analytics, continuous audit, and internal auditors’ skills and competencies had a positive correlation with CS quality, except for auditor independence. This research contributes to the limited research on CS quality factors and provides a guide for practitioners and researchers to improve the quality of internal audit functions in risk management and strategy development.